The Effect of Administration of Binahong Leaf Boiled Water on Accelerating the Healing of Perineal Wounds for Pubter Mothers - Apriyanti, Popy; Aini, Apriyanti; Lamdayani, Rinda (GLOBAL HEALTH SCIENCE GROUP, 2024)
A perineal wound or tear is an injury to the perineal area caused by an epistomy or natural laceration. One preventive measure to reduce the incidence of infection in postpartum mothers is to treat perineal wounds. The antiseptic content of the binahong plant can kill germs, increase resistance to infection, and speed up wound healing. This study aims to determine the effect of giving boiled water from binahong leaves on accelerating the healing of perineal wounds in postpartum mothers. This type of research is quantitative with a quasi-experimental design with Posttest Only Control Group Design. The population of this study was all postpartum mothers, totaling 30 respondents. The sample in this study consisted of 5 respondents who were given boiled water from binahong leaves (intervention) and 5 respondents who were not given boiled water from binahong leaves (control). Bivariate analysis was carried out using statistical tests to test mean dependent differences, namely the independent t-test, with a confidence level (α) = 0.05. The results of the study showed that there was a significant effect of giving boiled water from binahong leaves on accelerating perineal wound healing in postpartum mothers, with a p-value of 0.007. Where the significance value is smaller than the α value of 0.05. The conclusion of this study is that H0 is rejected, meaning that there is a significant difference in the acceleration of healing of perineal wounds between the intervention group and the control group.